Analysis of the interaction of lipases with polypropylene of different structure and polypropylene-modified glass surface - Foresti, María Laura; Ferreira, María Luján (Colloids and Surfaces A: Physicochemical and Engineering Aspects)
The hydrophobic/hydrophilic characteristics of the surface exposed by a lipase support conditions the amount of adsorbed protein, and probably also the conformation of the immobilized lipase. In reference to polypropylene (PP) – hydrophobic – in this study the polymer obtained with metallocene catalysts (PPmet) showed the best characteristics for the immobilization of lipase from Candida antarctica B in terms of surface structure and particle size. On the other hand, commercial pellets of polypropylene obtained with Ziegler-Natta catalysts (PPZN) showed to have lower affinity for proteins, which we attribute to a combination of higher particle size and different exposed surface. Despite its high affinity for proteins, low mechanical resistance of PPmet prohibited its use as lipase support in reactive systems with high mechanical efforts, such as strongly magnetically stirred batch laboratory reactors. Coating of glass balls with the polymer was attempted in order to confer better mechanical properties to PPmet. Mixed surfaces of PPmet/glass balls pre-treated with an acid/base protocol to generate surface OH successfully allowed biocatalyst recovery and reuse. However, the hydrophobic–hydrophilic surface generated could not resemble the strong active protein bonding achieved with powdered metallocenic polypropylene. Lipase adsorption over uncovered glass regions is proposed to be the reason for the differences found. Fil: Foresti, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina